Influence of mental health stigma on behavioral health evaluations - Taylor, Stephanie Leigh (2021)
Individuals in leadership roles in the military are in unique and complex positions to make the most ethical decisions to protect the mission and fellow soldiers on deployments. These difficult decisions may negatively impact the career of a soldier but are essential to fulfil the role of a military leader. Currently, a large database of literature explores mental health stigma; however, little to no research explores the impact of mental health stigma on decision-making processes in the context of deployments. The purpose of the current study was to explore how mental health stigma associated with post-traumatic stress disorder, depression, and alcohol use influence evaluations and decisions to deploy soldiers with a history of mental health diagnosis. This study used an experimental design with vignettes to simulate a military deployment assessment in which participants were asked to rate the likelihood that they would deploy the soldier from the vignette. Additionally, the current study worked to further explore personality traits associated with mental health stigma and examine the differences in stigma between the civilian and military population. The total sample consisted of 202 participants; however, only a sample of 60 was used for the analyses, which is described further in the method section. Results did not reveal significant findings when testing whether or not different diagnoses were associated with varying levels of stigma. Higher ratings of stigma were associated with a lower likelihood to deploy a soldier with a history of a mental health diagnosis. Additionally, the results did not reveal significant findings in association with deployment decisions and specific personality traits. The limitations of the study are described more fully below.